DIRECT FOREIGN INVESTMENTS IN KAZAKHSTAN: STATE AND PROBLEMS - Ye. N. Nesipbekov,; G.N.Appakova, (Academic Journal of Physical and Chemical Sciences, 2019)
The purpose of the study is to make a comprehensive assessment of the attracted foreign investments into the economy of Kazakhstan, and to identify the problems of its attracting. The work used general scientific methods of research: analysis and synthesis, statistical, graphical, methods of comparison and modeling. In particular, the study is based on a system analysis of the factors determining the dynamics of FDI in the country and its regions, and statistical methods for analyzing the national characteristics of FDI traffic in modern conditions. The article analyzes the dynamics of attracting foreign direct investment in modern conditions, allowing to assess the existing investment attractiveness of the country and its regions. The paper also identified the main problems that prevent foreign investment in the domestic economy. It is determined that foreign direct investments in the Kazakh economy are concentrated in raw materials industries and industries with a rapid return on capital with relatively little attention to high-tech industries that produce products with a high share of added value. All this makes it necessary to avoid dependence on raw materials and focus the main efforts on the industrialization of the national economy. The analysis of the regional distribution of foreign direct investment in Kazakhstan has shown their unevenness. Thus, it is revealed that the lion's share of FDI falls on 5 regions, 4 of which specialize in the raw material sector of production. It is shown that the investment attractiveness of the regions of our country for foreign investors is not the same and has significant interregional differences in the volume of foreign direct investment, which in turn requires the development of recommendations on the process of attracting foreign direct investment to the economy of the regions in order to increase their investment attractiveness. As a result of the study, the authors found the irrationality of the sectorial and regional structure of FDI distribution, which indicates the ineffectiveness of the mechanisms for attracting them to the economy of Kazakhstan. In this connection, the authors propose a set of measures aimed at implementing the new investment policy of the state, including changes in legislative acts, as well as measures to improve the economic mechanisms for FDI attracting.